Role and mechanisms of cytokines in the secondary brain injury after intracerebral hemorrhage. (July 2019) - Zhu, Huimin; Wang, Zhiqiang; Yu, Jixu; Yang, Xiuli; He, Feng; Liu, Zhenchuan; Che, Fengyuan; Chen, Xuemei; Ren, Honglei; Hong, Michael; Wang, Jian
Abstract: Intracerebral hemorrhage (ICH) is a common and severe cerebrovascular disease that has high mortality. Few survivors achieve self-care. Currently, patients receive only symptomatic treatment for ICH and benefit poorly from this regimen. Inflammatory cytokines are important participants in secondary injury after ICH. Increases in proinflammatory cytokines may aggravate the tissue injury, whereas increases in anti-inflammatory cytokines might be protective in the ICH brain. Inflammatory cytokines have been studied as therapeutic targets in a variety of acute and chronic brain diseases; however, studies on ICH are limited. This review summarizes the roles and functions of various pro- and anti-inflammatory cytokines in secondary brain injury after ICH and discusses pathogenic mechanisms and emerging therapeutic strategies and directions for treatment of ICH.